Long non-coding RNA NEAT1-centric gene regulation - Wang, Ziqiang; Li, Kun; Huang, Weiren (Cellular and molecular life sciences : CMLS, 2020)
Nuclear paraspeckle assembly transcript 1 (NEAT1) is a long non-coding RNA that is widely expressed in a variety of mammalian cell types. An increasing number of studies have demonstrated that NEAT1 plays key roles in various biological and pathological processes; therefore, it is important to understand how its expression is regulated and how it regulates the expression of its target genes. Recently, we found that NEAT1 expression could be regulated by signal transducer and activator of transcription 3 and that altered NEAT1 expression epigenetically regulates downstream gene transcription during herpes simplex virus-1 infection and Alzheimer’s disease, suggesting that NEAT1 acts as an important sensor and effector during stress and disease development. In this review, we summarize and discuss the molecules and regulatory patterns that control NEAT1 gene expression and the molecular mechanism via which NEAT1 regulates the expression of its target genes, providing novel insights into the central role of NEAT1 in gene regulation.